Rho-Kinase Inhibitors in the Management of Fuchs Endothelial Corneal Dystrophy: A Review - Anđela Jukić; Ana Pupić Bakrač; Biljana Đapic Ivančić; Andrijana Kopić; Ana Meter; Rajka Kasalica Žužul; Josip Pavan; Tomislav Jukić (Medicina)
Fuchs endothelial corneal dystrophy (FECD) is the most common corneal endothelial dystrophy. It is characterized by the progressive loss of corneal endothelial cells (CECs), guttae formation on the Descemet membrane, and corneal edema, leading to visual impairment. Corneal transplantation remains the standard treatment, but it has limitations such as donor shortages, infection risk, and graft rejection. Rho-kinase (ROCK) inhibitors have emerged as a promising pharmacological alternative. These agents promote CEC proliferation, migration, and adhesion while inhibiting apoptosis and enhancing corneal endothelial wound healing. Several studies have demonstrated the efficacy of ROCK inhibitors in improving corneal clarity and endothelial function, particularly when used as an adjunct to Descemet Stripping Only (DSO) surgery. Additionally, they show potential in preventing corneal edema in FECD patients undergoing cataract surgery. The methodology involved a literature search through the PubMed and Medline databases using relevant keywords. Only peer-reviewed articles in English were included, with additional references from selected articles reviewed to ensure comprehensive coverage. ROCK inhibitors offer a novel pharmacological approach to managing FECD. They have shown potential in promoting endothelial cell regeneration and improving corneal functIion. Despite promising results, further research is required to determine ROCK inhibitors’ long-term safety, optimal dosing, and efficacy in surgical and non-surgical FECD patients. Their potential to delay or prevent corneal transplantation represents a significant advancement in FECD management.